Psychological Capital and Non-Physical Work Environment on Millennial Generation Employees Work Engagement - Azatil Aqmar Roemy Aprillie; Hairani Lubis; Dian Dwi Nur Rahmah (Psikostudia : Jurnal Psikologi, 2022)
The millennial generation is the generation that will dominate the world of work. However, currently the millennial generation is known as a generation that likes to change jobs. It takes a good work engagement so that the millennial generation can survive in their work. This study aims to empirically examine whether there is an influence of psychological capital and non-physical work environment on work engagement in the millennial generation in Samarinda City. The subjects of this study were 355 millennial generation employees who were selected using purposive sampling technique. The measuring instrument used in this research is the work engagement scale, psychological capital scale, and non-physical work environment scale. Data analysis technique using multiple model regression test resulted in calculated F value = 177.435 > F table = 3.02, adjust R square = 0.502, and p = 0.000. These results indicate that there is an influence between psychological capital and non-physical work environment on work engagement in the millennial generation in Samarinda City. Generasi milenial merupakan generasi yang akan mendominasi dunia kerja. Namun, saat ini generasi milenial dikenal sebagai generasi yang suka berpindah pekerjaan. Dibutuhkan keterikatan kerja yang baik agar generasi milenial mampu bertahan dalam pekerjaannya. Penelitian ini bertujuan untuk menguji secara empirik ada atau tidaknya pengaruh modal psikologis dan lingkungan kerja non fisik terhadap keterikatan kerja pada generasi milenial di Kota Samarinda. Subjek penelitian ini adalah 355 orang karyawan generasi milenial yang dipilih menggunakan teknik purposive sampling. Alat ukur yang digunakan dalam penelitian ini adalah skala keterikatan kerja, skala modal psikologis, dan skala lingkungan kerja non fisik. Teknik analisa data menggunakan uji regresi model berganda menghasilkan nilai F hitung = 177.435 > F tabel = 3.02, adjust R square = 0.502, dan p = 0.000. Hasil tersebut menunjukkan terdapat pengaruh antara modal psikologis dan lingkungan kerja non fisik terhadap keterikatan kerja pada generasi milenial di Kota Samarinda.